Kynurenic acid ameliorates NLRP3 inflammasome activation by blocking calcium mobilization via GPR35 - Sun, Tianyin; Xie, Ruiqian; He, Hongbin; Xie, Qianqian; Zhao, Xueqin; Kang, Guijie; Cheng, Chen; Yin, Wenwei; Cong, Jingjing; Li, Jing; Wang, Xuefu (Frontiers in Immunology, 2022)
The inflammasome has been linked to diverse inflammatory and metabolic diseases, and tight control of inflammasome activation is necessary to avoid excessive inflammation. Kynurenic acid (KA) is a tryptophan metabolite in the kynurenine pathway. However, the roles and mechanisms of the regulation of inflammasome activation by KA have not yet been fully elucidated. Here, we found that KA suppressed caspase-1 activation and IL-1β production in macrophages by specifically inhibiting canonical and noncanonical activation of the NLRP3 inflammasome. Mechanistically, KA reduced calcium mobilization through G-protein receptor 35 (GPR35), resulting in reduced mitochondrial damage and decreased mtROS production, thus blocking NLRP3 inflammasome assembly and activation. Importantly, KA prevented lipopolysaccharide-induced systemic inflammation, monosodium urate-induced peritoneal inflammation, and high-fat diet-induced metabolic disorder. Thus, KA ameliorated inflammation and metabolic disorders by blocking calcium mobilization-mediated NLRP3 inflammasome activation via GPR35. Our data reveal a novel mechanism for KA in the modulation of inflammasome activation and suggest that GPR35 might be a promising target for improving NLRP3 inflammasome-associated diseases by regulating calcium mobilization.